2011
DOI: 10.1007/s10344-011-0592-0
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite-based genotyping of MHC class II DRB1 gene in Iberian and Alpine ibex

Abstract: In an analysis of a microsatellite locus (OLADRB1) linked to the MHC DRB1 gene of Iberian and Alpine ibex (Capra pyrenaica and Carpa ibex), we detected strong linkage disequilibrium between both loci. The allele length polymorphism at OLADRB1 was unambiguously linked to a particular DRB1 allele. This allowed us to develop a DRB-STR matching method for both ibex species. Validation of the DRB-STR matching method was performed in 160 Iberian ibex from Spain and 98 Alpine ibex from Switzerland and Italy. This sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…We extended the sequencing by Schaschl et al [27] and Alasaad et al [28] from 125 to 203 Alpine ibex from different populations and did not find additional alleles at the exon 2 of the MHC DRB locus. We found that the second allele ( Caib-DRB *2) was identical to the Cahi-DRB *16 allele of the domestic goat first reported from the Japanese breed Shiba ( [29] , Genbank accession AB008361).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…We extended the sequencing by Schaschl et al [27] and Alasaad et al [28] from 125 to 203 Alpine ibex from different populations and did not find additional alleles at the exon 2 of the MHC DRB locus. We found that the second allele ( Caib-DRB *2) was identical to the Cahi-DRB *16 allele of the domestic goat first reported from the Japanese breed Shiba ( [29] , Genbank accession AB008361).…”
Section: Resultsmentioning
confidence: 67%
“…The depletion of genetic variability is particularly striking at the DRB locus of the MHC class II. Only two alleles ( Caib-DRB *1 and Caib-DRB *2) were reported at the exon 2 of DRB in at total of 125 individuals [27] , [28] . In comparison, both the domestic goat ( C. aegagrus hircus ) and its wild ancestor the bezoar ( C. aegagrus ) are highly polymorphic at this exon.…”
Section: Introductionmentioning
confidence: 96%
“…Despite severe demographic changes over the past century, Iberian ibex were not affected by similar range and census reductions as Alpine ibex. The less severe bottlenecks experienced by Iberian ibex are reflected in higher genetic diversity at the major histocompatibility complex (MHC) (Alasaad et al, 2012;Amills et al, 2004).…”
mentioning
confidence: 99%
“…(e.g. Alasaad et al, 2012;Brambilla et al, 2018;Grossen et al, 2014). Underlining the relevance of performing large-scale targeted amplicon sequencing of immune loci are recent findings that high heterozygosity at the MHC was correlated with higher resistance to infectious keratoconjunctivitis, a major disease factor in some Alpine ibex populations (Brambilla et al, 2018).…”
Section: Discussionmentioning
confidence: 99%